Aplicación del sistema GRADE a las recomendaciones de pruebas diagnósticas en la Guía Colombiana de Falla Cardíaca (2016)
ABSTRACT: Clinical practice has an implicit degree of uncertainty as to the precise diagnosis, in relation to a cluster of symptoms and signs in the context of predisposing risk factors, detected during a careful and complete medical history. It is then required that clinicians are familiar with the properties of diagnostic tests, in order to use them properly and not as a fruitless and unspecific research. Methodology: We reviewed the operational characteristics of diagnostic tests, including sensitivity, specificity, positive and negative predictive values, positive and negative likelihood ratio (LR), and ROC curves, which serve as bases for establishing the recommendations on diagnostic tests in the GRADE system in the Colombian Guideline for Heart Failure. Results: We explain how to make the qualification of diagnostic tests with the GRADE methodology, taking into account their operating characteristics, and the variables that influence the grading of recommendations, such as the risk of biases, the character of directness or not of the test, the presence of inconsistency or imprecision, and the publication bias. Conclusion: GRADE methodology rating of evidence in diagnostic tests allows their complete assessment, both in the operational characteristics and in the application to clinical practice.